Education, prevalence of disease, and frequency of health care utilisation. The 1983 Italian National Health Survey. Issue 2 (June 1987) - La Vecchia, C; Negri, E; Pagano, R; Decarli, A
Abstract : The relation between education, prevalence of 17 chronic diseases or groups of diseases, and pattern of health care utilisation was evaluated from data from the 1983 Italian National Health Survey, based on 58 462 individuals aged 25 or over randomly selected within strata of geographical area, size of place of residence, and size of household, in order to be representative of the whole Italian population. Most of the diseases considered, including diabetes, hypertension, myocardial infarction and other heart disease, haemorrhoids or varices, chronic respiratory disease, anaemias, gastroduodenal ulcer, cholelithiasis and liver cirrhosis, kidney and urological diseases, arthritis, and psychiatric and neurological disturbances, were consistently less prevalent among more educated individuals. The age and sex adjusted risk estimates for individuals educated in high school or university compared with those with only a primary school education or less ranged between 0.21 for liver cirrhosis and 0.80 for anaemias. The sole exception was allergy, which was more prevalent among the more educated individuals (relative risk = 1.42). General practitioner visits and hospital admissions were reported less frequently by the more educated individuals, but specialist consultations of potential preventive value were less frequent among the less well educated. The results were similar when occupation was utilised as an indicator of social class. Thus, the findings of this national survey provide confirmation and quantitative assessment of considerable differences in health and health service utilisation according to indicators of social class.